Al-Zeer Salem at Alfred Faraj Theater (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research is based on a theatrical study of the plays of Alfred Faraj, which was considered by critics to be a distinctive creativity, the play Al-Zeer Salem. The research will attempt to show the relationship between heritage on the one hand and modern literary art on the other, and to what extent the impact of Arab heritage and the Arab popular biographies on Alfred theatrical creativity at the level of form first and content second.